Developing a generic model of program accreditation in Iran - Fariba Jokar; Nikoo Yamani; Maryam Avizhgan; Tahere Changiz (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: Higher education plays an important role in the development of countries in social, economic, cultural, and scientific aspects. Also, the field of healthcare is changing rapidly, and to provide better care, health professional students need to be trained at a higher level. This situation has placed demands on academic and clinical settings responsible for training professional health students. The main objectives of this research project can be defined as 1 -to investigate important issues of accreditation and assessment process of health professional education worldwide and 2-to design and develop a uniform, transparent, and scientific accreditation framework for health professional programs in Iran.METHODS AND MATERIAL: The research methodology for the design of a generic accreditation framework in health professional education is outlined by the following step-by-step (1 to 7) procedure according to the developmental research methodology and three phases considering analysis, development, and evaluation.RESULTS: The findings of the analysis phase showed that there is no specific structure and process for accreditation in Iran compared to other countries. The three most common actions of the accreditation include the following: 1. self- assessment, 2. peer-review and site visits, and 3. evaluation and reports. A review of the relevant literature and websites indicate that various assessment frameworks have been developed regionally, as well as internationally, to accredit professional health programs. However, most of these frames seem to be non-uniform, too complex, and non-transparent. In addition to these results, three themes were extracted from the interview analysis, "accreditation barrier," "theoretical foundation of accreditation," and "specific structure and process of accreditation" which indicates the need for education at various levels of educational managers and faculty members. Therefore, these issues were taken into consideration in the design of the accreditation framework of health professional educational programs. After two stages of evaluation from the point of view of specialists and experts of the educational secretariats of the Ministry of Health and Medical Education, the final version of the program's accreditation framework and policy will be finalized.CONCLUSION: In Iran, despite the challenges and valuable activities in different educational secretariats, there was no coherent process that can be considered accreditation. In this study, self-study evaluation guide, external evaluation, standard development, and ethical guide for the programs accreditation were developed. The results of this study can help the educational secretariats of the Health and Medical Education Ministry that is based on the documents developed and operationalize their accreditation process and structure.